Agribusiness value impacts from highly pathogenic avian influenza. Issue 3 (3rd June 2019) - Thompson, Jada M.; Trejo-Pech, Carlos J.O.; Pendell, Dustin L.
Abstract : Purpose: The purpose of this paper is to determine the impact of 2014–2015 highly pathogenic avian influenza (HPAI), the largest animal health emergency in US history to date, on agribusinesses' market values. Design/methodology/approach: Using the 2014–2015 HPAI outbreaks in US commercial poultry, event study analysis of meat processing and marketing companies is conducted to estimate the effects HPAI had on firm value and how these effects differed across meat marketing firms over distinct disease event dates. The analyses include an overall aggregate event study, chronological outbreak studies, and an analysis that separated firms specifically marketing poultry products from those marketing all other types of meat. Findings: By tracing abnormal stock returns through the event dates, the results show heterogeneity of investors responses based on the nature of the event (i.e. backyard vs commercial flocks affected), timing of the event over the course of the entire HPAI outbreak, and if a firm marketed poultry products. Overall, negative abnormal returns, ranging from 2 to 4 percent of publicly traded meat processors' equities, are predominant post-disease event. These negative effects are slightly higher, above 5 percent, for firms marketing poultry products. Originality/value: This study is the first to analyze the effects of an HPAI outbreak on the market value of US agribusiness firms.